Sex-specific associations between alcohol consumption, cardiac morphology, and function as assessed by magnetic resonance imaging: insights form the UK Biobank Population Study. (12th December 2020) - Simon, Judit; Fung, Kenneth; Kolossváry, Márton; Sanghvi, Mihir M.; Aung, Nay; Paiva, Jose Miguel; Lukaschuk, Elena; Carapella, Valentina; Merkely, Béla; Bittencourt, Marcio S.; Karády, Júlia; Lee, Aaron M.; et al.
Abstract: Aims: Data regarding the effects of regular alcohol consumption on cardiac anatomy and function are scarce. Therefore, we sought to determine the relationship between regular alcohol intake and cardiac structure and function as evaluated with cardiac magnetic resonance imaging. Methods and results: Participants of the UK Biobank who underwent cardiac magnetic resonance were enrolled in our analysis. Data regarding regular alcohol consumption were obtained from questionnaires filled in by the study participants. Exclusion criteria were poor image quality, missing, or incongruent data regarding alcohol drinking habits, prior drinking, presence of heart failure or angina, and prior myocardial infarction or stroke. Overall, 4335 participants (61.5 ± 7.5 years, 47.6% male) were analysed. We used multivariate linear regression models adjusted for age, ethnicity, body mass index, smoking, hypertension, diabetes mellitus, physical activity, cholesterol level, and Townsend deprivation index to examine the relationship between regular alcohol intake and cardiac structure and function. In men, alcohol intake was independently associated with marginally increased left ventricular end-diastolic volume [ β  = 0.14; 95% confidence interval (CI) = 0.05–0.24; P  = 0.004], left ventricular stroke volume ( β  = 0.08; 95% CI = 0.03–0.14; P  = 0.005), and right ventricular stroke volume ( β  = 0.08; 95% CI = 0.02–0.13; P  = 0.006). In women, alcohol consumption was associated with increased left atrium volume ( β  = 0.14; 95% CI = 0.04–0.23; P  = 0.006). Conclusion: Alcohol consumption is independently associated with a marginal increase in left and right ventricular volumes in men, but not in women, whereas alcohol intake showed an association with increased left atrium volume in women. Our results suggest that there is only minimal relationship between regular alcohol consumption and cardiac morphology and function in an asymptomatic middle-aged population.